2015
DOI: 10.12659/pjr.892758
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Safety Awareness Among Medical Staff

Abstract: SummaryBackgroundThe common access to imaging methods based on ionizing radiation requires also radiation protection. The knowledge of ionizing radiation exposure risks among the medical staff is essential for planning diagnostic procedures and therapy.Evaluation of the knowledge of radiation safety during diagnostic procedures among the medical staff.Material/MethodsThe study consisted of a questionnaire survey. The questionnaire consisted of seven closed-ended questions concerning the knowledge of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 1 publication
0
11
1
1
Order By: Relevance
“…Szarmach et al state that radiation safety can only be addressed by educating all healthcare professionals, irrespective of their position, and that they need to be trained ‘thoroughly and systematically’. 23 Reinforcing radiation safety messages and training optimises radiation safety. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Szarmach et al state that radiation safety can only be addressed by educating all healthcare professionals, irrespective of their position, and that they need to be trained ‘thoroughly and systematically’. 23 Reinforcing radiation safety messages and training optimises radiation safety. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Uniformity in content and instruction will facilitate that interventionalists are adequately trained in this area and that radiation safety is reinforced across South Africa. 1 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…The anesthesiologist is exposed to high levels of radiation in the radiology intervention room [ 27 ] during fluoroscopy and must wear proper protective lead aprons and thyroid shields throughout the procedure [ 28 ]. Szarmach et al [ 29 ] reported that radiation safety among medical staff was lowest in the surgical ward. Physicians as well as trainees and students should be equipped with dosimeters where there is evident radiation exposure, despite their low radiation exposure.…”
Section: Environmentmentioning
confidence: 99%
“…Lacking any validated questionnaires for RP, an ad hoc questionnaire was developed based on several bibliographic sources [15,16,19,[26][27][28] and distributed before and after training. The questionnaire was nominative to compare pre/post training responses and included When the x-ray tube is horizontal, you position yourself:…”
Section: Questionnairementioning
confidence: 99%